Отходы промышленности – эффективное сырье для создания низкообжигового керамического композита - Деревянко, Виктор Николаевич; Дерев’янко, Віктор Миколайович; Derevianko, Viktor; Гришко, Анна Николаевна; Гришко, Ганна Миколаївна; Hryshko, Hanna (My University, 2017)
Експериментально підтверджено, що при повній заміні природної суглинистої сировини на вторинні продукти збагачення ільменітової руди Вільногірського гірничо- металургійного комбінату (ВГМК) з додаванням 40 % мулу ЦСА і 10 % залізовмісних відходів відбувається збільшення показників міцності і зниження щільності і температури випалу. При 870 oC температура межі міцності при стисненні збільшується з 14,5 до 21,89 МПа, щільність становить 1350 кг/м3. Фізико-хімічними методами визначено, що підвищення міцнісних показників пов'язане з утворенням мональбіту – 34,6 %; альбіту – 4,3 %, геленіту – 7,6 %. Due to depletion of high-quality natural raw material resources combined with build-up of reserves of man-made industrial products, waste disposal problem becomes a topical issue particularly in the industrial regions. One of the ways to solve the industrial waste problem is to use wastes for producing ceramic materials. Investigated were compositions with various contents of components: secondary ilmenite ore concentration products from VGMK, sludge and ironcontaining wastes. It has been found that the VGMK wastes are represented by finely dispersed particles, and local liquefaction areas occur at the temperature of 480-500°C. The basic sintering temperature is 1,050°C. It has been found that the increase of the sludge content in the molding compound from 30 to 40 % results in the decrease in the basic liquid phase amount occurrence temperature from 950 to 820°C, or by 13,6 %. Using the mathematical methods of experiment design a pattern has been determined of the strength and density variation depending on a molding compound composition, namely, the content of iron-containing waste and sludge. It has been experimentally confirmed that the complete replacement of natural clay-loam materials by secondary ilmenite ore concentration products from Volnogorsk Mining-and-Metallurgical Integrated Works (VGMK) with the addition of 40 % of CSA sludge and 10% of iron-containing waste results in both strength performance improvement and density and firing temperature reduction. At a temperature of 870°C, the ultimate compressive strength has been increased from 14,5MPa to 21,89MPa, and the density has reached 1350 kg/m3. Using physical and chemical methods it has been determined that the strength performance improvement is due to formation of monalbite – 34,6 %; albite – 4,3 %, gehlenite – 7,6 %.
Відходи промисловості – ефективна сировина для створення низьковипалювального керамічного композита
Industrial waste as an effective raw material for producing the low-fired ceramic composite
Keywords: керамічна цегла; ceramic brick; мул; sludge; залізовмісні відходи; iron-containing waste; техногенна сировина; man-made raw material; міцність; strength